Extract of Red Okra Pod (Abelmoschus esculentus L. Moench) Chemoprevents N-Methyl-N-Nitrosourea-Induced Kidney Proximal Tubular Cells Damage - Achhlam, Divany Hunaimatul; Wahyuningsih, Sri Puji Astuti; Hapsari, Lukiteswari Dyah Tri; Soepriandono, Hari; Dewi, Firli Rahmah Primula (HAYATI Journal of Biosciences, 2024)
N-Methyl-N-Nitrosourea (MNU) is a compound that induces oxidative stress resulting in high levels of oxidants and damage to body cells. Red okra contains polyphenol and flavonoid active ingredients as antioxidants. This study aims to analyze the effect of ethanol extract of red okra pods (ROPE) on oxidant levels, antioxidant enzymes, and damage to rat kidney proximal tubule cells due to NMU. This study used 30 rats divided into six treatment groups, namely CN (normal), N (negative control; MNU 50 mg/kg BW), P (positive control; MNU and MTX 50 mg/kg BW), T1 (MNU and ROPE 50 mg/kg BW), T2 (MNU and ROPE 100 mg/kg BW), and T3 (MNU and ROPE 200 mg/kg BW). The treatment was carried out on all groups after eight weeks. The results indicate that malondialdehyde (MDA) and nitrogen oxide (NO) decrease with the ROPE treatment. The glutathione reductase (GSH) activity as an antioxidant enzyme increased T1 and T2, while glutathione peroxidase (GPx) showed an increase in T2 and T3. Furthermore, the biochemical marker of the rat kidney showed lower blood urea nitrogen (BUN) and creatinine (Cre) levels in all treatment groups. Then, the repair of damaged proximal tubule cells showed an increase in normal cells and lower swollen cells; however, there was a degradation in necrotic cells in T2 and T3. It can be indicated that the ROPE can act as an antioxidant that can reduce MDA and NO levels, increase GSH and GPx levels, and reduce damage to proximal renal tubule cells due to MNU.